A transformação da criatividade por meio da IA: análises dos temas e convergência entre eles - Oliveira, Leilane Alves Borges de (2025)
Introduction: This dissertation is a analict review of specialized literature on the intersection of Creativity and Generative Artificial Intelligence. Aim: The goal is to understand the current discussions on the creativity transformation through AI. Method: To do so, it was necessary to seek an understanding of the fundamental concepts of each field separately, and then examine the articles focused specifically on the convergence of the two themes. Two theories of Creativity considered relevant in the mainstream of Behavioral Psychology were analyzed, and the functioning of AI was presented based on the evolution of the theme, starting with data analysis using algorithms that led to machine learning, moving on to deep learning with neural networks, until the emergence of Generative AI. Results: The articles analyzed address possibilities still little explored in the intersection between the two themes and present important questions that remain open in this context. The authors approach generative artificial intelligence only from the results obtained viewpoint, failing to consider the mechanistic and unintentional means in which they were produced. Discussion: This indicates a need for closer collaboration among researchers in these areas to deepen the debate